153k views
1 vote
Which equation has no solution?

4(x + 3) + 2x = 6(x + 2)
5+2(3 + 2x) = x + 3(x + 1)
5(x + 3) + x = 4(x + 3) + 3
4 + 612 + x) = 2(3x + 8)

User Snifff
by
5.4k points

2 Answers

7 votes

Answer:


  1. 4(x + 3) + 2x = 6(x + 2)

  2. 5 + 2(3 + 2x) = x + 3(x + 1)

Explanation:


5(x + 3) + x = 4(x + 3) + 3 \\ 5x + 15 + x = 4x + 12 + 3 \\ 5x + x - 4x = 12 + 3 - 15 \\ 2x = 0

Divide both sides of the equation by 2

2x/2 = 0/2

x = 0

(4+612+x)=2(3x+8)

4+612+x=6x+16

4+612-16=6x-x

600=5x

Divide both sides of the equation by 5

600/5 = 5x

120 = x

User Olovb
by
5.2k points
6 votes

Answer:

Its B. 5+2(3 + 2x) = x + 3(x + 1)

Explanation:

I just took the test on edge

User Gunter Hager
by
6.2k points